2021
DOI: 10.3390/biology10030245
|View full text |Cite
|
Sign up to set email alerts
|

Structural Biology and Structure–Function Relationships of Membrane Proteins

Abstract: To understand the biological complexity of life, one needs to investigate how biomolecules behave and interact with each other at a molecular level [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…This study found significant difference in final protein yields between the two protocols, with the protein yield from K562 higher when utilizing Protocol 2, compared with protein concentration yield when using Protocol 1. This current adapted protocol is supported by previous investigations that reported wide variations in protein yield and reproducibility by existing protein extraction methods, which has been widely reported as a big challenge in membrane proteomic studies (Alberts et al, 2002;Bünger et al, 2009;Grabski, 2009;Lin and Guidotti, 2009;Janson, 2012;Lai, 2013;Scheiter et al, 2013;Kubicek et al, 2014;Grant, 2016;Lee, 2017;Reis and Moraes, 2019;Birch et al, 2020;Moraes and Quigley, 2021). No one cell disruption approach is better since each of these approaches has limitations and challenges.…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…This study found significant difference in final protein yields between the two protocols, with the protein yield from K562 higher when utilizing Protocol 2, compared with protein concentration yield when using Protocol 1. This current adapted protocol is supported by previous investigations that reported wide variations in protein yield and reproducibility by existing protein extraction methods, which has been widely reported as a big challenge in membrane proteomic studies (Alberts et al, 2002;Bünger et al, 2009;Grabski, 2009;Lin and Guidotti, 2009;Janson, 2012;Lai, 2013;Scheiter et al, 2013;Kubicek et al, 2014;Grant, 2016;Lee, 2017;Reis and Moraes, 2019;Birch et al, 2020;Moraes and Quigley, 2021). No one cell disruption approach is better since each of these approaches has limitations and challenges.…”
Section: Discussionmentioning
confidence: 59%
“…Membrane protein isolation is a multiple steps process, and various approaches are used to disrupt cell membranes including mechanical-based techniques such as sonication, French press and grinding as well as nonmechanical-based approaches such as osmotic shock, freeze thawing and detergent-based approaches (Lin and Guidotti, 2009;Janson, 2012). Cell lysis liberates various cell contaminating molecular species, inevitably disrupting, and potentially compromising the structural and functional integrity of membrane proteins (Birch et al, 2020;Moraes and Quigley, 2021). Removal of interfering substances can be achieved by various techniques including acid, salt, and alcohol precipitation methods, usually combined with differential centrifugation (Janson, 2012;Birch et al, 2020;Moraes and Quigley, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations